PENGARUH STRES KERJA, PELATIHANKERJA, DANLINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA PERUM BULOG SUB DIVRE JEMBER - Hardjono Hardjono; Lailatul Nur Makkia; Riska Ayu Pramesthi (Relawan Jurnal Indonesia, 2019)
This study aims (1) to determine the effect of work stress, job training, and work environment partially influential on employee performance (2) to determine the effect of work stress, job training, and work environment simultaneously influence on employee performance (3) to find out among work stress , job training, and the most dominant work environment influences employee performance. The method used is qualitative. The results of the study are multiple linear regression equation Y = 5,347E-17 + 0.032 X1 + 0.224 X2 + 0.610 X3 + e. Partially work stress has a significant negative effect with tcount greater than ttable (0.129)> (2,208), job training shows tcount greater than ttable (-0,922)> (2,208), work environment shows tcount greater than ttable (ttable (t20) 4,471)> (2,208). Simultaneously, work stress, job training, and work environment affect the performance of employees with a calculated F value of 19.210 values ​​greater than the F table of 2.87. The variable that has the most dominant influence in this study is the work environment with a value of 4.471. The coefficient of determination of the influence of independent variables on the dependent variable was 61.6% while 38.4% was influenced by other variables not included in the study.